Cutaneous squamous cell carcinomas on special locations: perioral, periocular and genital area. (13th December 2019) - Nägeli, M.C.; Ramelyte, E.; Dummer, R.
Abstract: If tumours arise in special locations such as around the eyes, mouth or in the genital area, patients and physicians are challenged by the need for complete removal of the tumour with safety margins and high demands on function and aesthetic aspects. Treatment should be performed by specialized physicians including ophthalmologists, head and neck surgeons, surgical, medical and radiation oncologists. The first‐line treatment for most cutaneous malignancies is surgical excision; however, in several situations, such as well‐differentiated cutaneous squamous cell carcinomas (cSCC) in the periocular or anal region, radiotherapy is a very reasonable and sometimes treatment of first choice, especially in patients with advanced age. In periocular SCC, radiotherapy with superficial x‐ray combined with eye shielding, while in anal SCC, radiotherapy combined with chemotherapy is recommended. However, after failure of local treatment options including surgery and radiotherapy, systemic medications are indicated in order to achieve tumour control or cure. Systemic therapies include immunotherapy, targeted therapy or chemotherapy. Preventive strategies are based on UV protection in facial, and vaccination in HPV associated anogenital SCCs.